Mehr Transparenz durch das Lobbyregister? - Andreas Polk (Wirtschaftsdienst, 2021)
In Deutschland soll ein Lobbyregister eingeführt werden. Fraglich ist, ob das vorgesehene Gesetz ausgewogene Regelungen vorsieht, um für hinreichende Transparenz in der Einflussnahme zu sorgen. Die vorgeschlagenen Maßnahmen reichen nicht aus, um die Einflussnahme vollständig und aktuell abzubilden. – – This paper analyses Germany's proposed lobbying register. While the declared existence of the political will to introduce such a register is an improvement per se, the proposal lacks scope and provides too many loopholes. First, the list of exemptions with respect to who counts as a lobbyist releases important groups from reporting at all. Second, the proposal should implement a quarterly reporting obligation in order to allow comprehensive insights into how lobbyists influence policy proposals. Third, reporting should be more detailed with respect to the staff and financial resources employed. It should also identify who is active as a lobbyist and who they contact.
Keywords: D72; D73; D02; 330